Retinitis Pigmentosa with Congenital Sensorineural Hearing Loss: Ushers Syndrome - M H Patil; Piyushi Sao (Wolters Kluwer Medknow Publications, 2020)
Background: Retinitis pigmentosa or pigmentary retinal dystrophy denotes a clinically and genetically diverse group of inherited diffuse retinal degenerative diseases. The classic triad of findings comprises bony spicules, retinal pigmentation, arteriolar attenuation and waxy disc pallor. Ushers syndrome is autosomal recessive disorder characterized by sensorineural hearing loss or deafness and progressive vision loss due to retinitis pigmentosa. The key features of the rod-cone type of disease are progressive night blindness and tunnel vision, symptoms that become more severe as more rods die. Typically, both eyes are affected similarly. Case Discussion: As told by informant (patient's brother) 45-year male who is deaf and dumb since birth presented with chief complaint of difficulty in seeing in night since 19 years and diminution of vision of both eyes during day time also since last 4 years. Ocular Examination: the patient had posterior subcapsular cataract in visual axis in both eyes. FUNDUS: Bony spicules shaped pigments over mid periphery extending posteriorly; decreased A-V ratio; blood vessels showing arteriolar attenuation; tessellated background with retinal pigment epithelium atrophy. Family History: Patient is deaf and dumb since birth. Pedigree suggest autosomal recessive pattern of inheritance. Vestibular Function: RINNE: Positive; WEBER: central ABC: decreased in both ears (with 512 Hz) Conclusion: Patient has Retinitis Pigmentosa along with posterior subcapsular cataract which is one of the common associations in patients of RP. Patient also has sensorineural hearing loss which needs to be confirmed with pure tone audiometry. These findings fit into diagnosis of Ushers Syndrome.